2018
DOI: 10.1136/neurintsurg-2017-013697
|View full text |Cite
|
Sign up to set email alerts
|

Arterial diameter and the gender disparity in stroke thrombectomy outcomes

Abstract: These results provide limited evidence that males have larger cerebral arterial diameters than females and that larger arterial diameters may improve the odds for favorable clinical outcomes. If future studies validate these findings, arterial diameter may become a relevant variable in the design of improved thrombectomy strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…Our findings also add to the literature by demonstrating sex differences in outcomes after mechanical thrombectomy in a non-clinical trial population and are thus potentially generalizable to other populations of patients with LVOs treated with thrombectomy at other geographic locations and institutions. Of note, one previous study of sex differences in outcomes after thrombectomy suggests that smaller intracerebral vessel diameter could be a contributor to such differences 11. In this particular study, both the ICA and MCA were smaller in females than males, but neither sex nor vessel diameter were significant predictors of outcome in multivariate analyses 11.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Our findings also add to the literature by demonstrating sex differences in outcomes after mechanical thrombectomy in a non-clinical trial population and are thus potentially generalizable to other populations of patients with LVOs treated with thrombectomy at other geographic locations and institutions. Of note, one previous study of sex differences in outcomes after thrombectomy suggests that smaller intracerebral vessel diameter could be a contributor to such differences 11. In this particular study, both the ICA and MCA were smaller in females than males, but neither sex nor vessel diameter were significant predictors of outcome in multivariate analyses 11.…”
Section: Discussioncontrasting
confidence: 52%
“…Of note, one previous study of sex differences in outcomes after thrombectomy suggests that smaller intracerebral vessel diameter could be a contributor to such differences 11. In this particular study, both the ICA and MCA were smaller in females than males, but neither sex nor vessel diameter were significant predictors of outcome in multivariate analyses 11. The study, however, was underpowered to detect outcome differences by sex or vessel diameter 11…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies reported that females consistently fare worse than males following MT for large vessel ischemic stroke [ 16 , 17 ]. One of the possible reasons is that males have larger cerebral arterial diameters than females, which may improve the odds for favorable clinical outcomes [ 18 ]. Serum creatinine is widely used as an indicator of renal function, and impaired renal function is also associated with long-term mortality and poor prognosis after stroke [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that females consistently fare worse than males following MT for large vessel ischemic stroke [11,12]. One of the possible reasons is that males have larger cerebral arterial diameters than females, which may improve the odds for favorable clinical outcomes [13]. Serum creatinine is widely used as an indicator of renal function, and impaired renal function is also associated with long-term mortality and poor prognosis after stroke [14].…”
Section: Nomogram Variables Interpretationmentioning
confidence: 99%